Effectiveness of Implement Mathematics Curriculum in Classroom of Secondary Level - Yadav, Keshab Ram (Journal of Rapti Babai Campus, 2026)
This research study evaluates the effectiveness of mathematics curriculum implementation in the classrooms of secondary schools in Rajpur Rural Municipality, Dang. The research design is qualitative and follows the interpretivist paradigm. Data were collected through focus group discussions with nine students and in-depth interviews with mathematics teachers from three secondary schools. Student academic achievement is a crucial indicator of the overall quality of school education in Nepal; however, the achievement level in community schools remains low, particularly in grade ten mathematics. This issue poses a significant challenge for teachers, students, parents, and the local government of Rajpur Rural Municipality. Findings indicate that teachers rely heavily on textbooks and do not adequately use the curriculum in classroom practice. Large class sizes, poor foundational knowledge of students, limited understanding of learners’ interests and abilities, and insufficient familiarity with the new curriculum were identified as major barriers. Additionally, teachers lack updated training and adequate knowledge of information and communication technologies (ICT) for classroom use. To enhance students’ academic achievement and strengthen Nepal’s overall educational system, improved and effective use of the new curriculum across its various components is essential.